Humanistic geography in an indigenous community of Mexico: Santa Catarina Lachatao - García-Luna Romero, Ana C.; Quiroga-Garza, Angélica (Frontiers in Sustainable Cities, 2023)
Introduction The present study aim was to rethink the geographical reasoning of everyday life toward a new understanding of knowing how to think about space through an interdisciplinary approach, architecture-psychology. This allowed establishing logical relations in spatial and socio-spatial distributions and uses of social phenomena, typical of Santa Catarina Lachatao, an indigenous Mexican community in Sierra Norte Zapoteca. Methods Based on ethnographic qualitative interdisciplinary research methods along with a total of three visits lasting 15 weeks, the daily experience of people and their community in different times and spaces, experiences, perspectives, and prejudices, were studied. The geographical approach (cartographies) reflects the social construction of the spatial components as the basic understanding of the territory from everyday life. In this study we worked on indigenous citizenship and its territory, analyzing, and contrasting social phenomena such as power-subjection, wealth-poverty, and exclusion-inclusion that transversally allow us to reflect and understand some of the characteristics of diversity and territoriality of the indigenous communities in Mexico. Results Characteristics that predominating in indigenous communities was recognized and featured. This was observed in the social production of their public space which evidence intergenerational pride and sense of community and belonging and their commitment to preserve their life project sustaining their space, community, and traditions. The natural rural context emerges from the interplay between the natural landscape and the built environment (in constant expansion). The bodies of water are respected and protected by the community and the original crossings are still preserved as precious resources, just as any other natural element. Landscape takes precedence over the irregular built environment, reflected in the urban trace. Discussion Developing interdisciplinary research -architecture and psychology–allowed studying the community development of a Mexican indigenous community, respectfully approaching diversity and territoriality of Santa Catarina Lachatao, Oaxaca. Societies must be understood in and by means of space. Public policy is crucial to strengthen the autonomy and configuration of indigenous communities, warranting their active participation in the design and evaluation of government programs that favor the sustainable use of their lands and natural resources, as well as the preservation of their values and traditions. The principles of justice are chosen behind a veil of ignorance. John Rawls